Do Comorbid Social and Other Anxiety Disorders Predict Outcomes during and after Cognitive Therapy for Depression? - Vittengl, Jeffrey R. (J Affect Disord, 2018)
BACKGROUND. Cognitive therapy (CT) improves symptoms in adults with major depressive disorder (MDD) plus comorbid anxiety disorder, but the specific type of anxiety may influence outcomes. This study compared CT outcomes among adults with MDD plus social, other, or no comorbid anxiety disorders. METHODS. Outpatients with recurrent MDD (N=523, including 87 with social and 110 with other comorbid anxiety disorders) received acute-phase CT. Higher risk responders (n=241 with partial or unstable response) were randomized to 8 months of continuation treatment (CT or clinical management plus fluoxetine or pill placebo), followed by 24 months of assessment. Lower risk responders (n=49) were assessed for 32 months without additional research treatment. Depression, anxiety symptoms, and social avoidance were measured repeatedly. RESULTS. Other (non-social), but not social, anxiety disorders predicted elevated depression and anxiety symptoms throughout and after acute-phase CT. Social, but not other, anxiety disorder predicted greater reduction in depressive symptoms during acute-phase CT and elevated social avoidance during and after acute-phase CT. LIMITATIONS. Anxiety disorders were assessed only before acute-phase treatment. The anxiety symptom measure was brief. Generalization to other patient populations and treatments is unknown. CONCLUSIONS. Non-social comorbid anxiety disorders may reduce the efficacy of acute-phase CT for MDD by diminishing both short-and longer term outcomes relative to depressed patients without comorbid anxiety disorders. Comorbid social anxiety disorder may increase relative reductions in depressive symptoms during acute-phase CT for MDD, but patients with comorbid social anxiety disorder may require specialized focus on social avoidance during CT.